The nicotinic acid receptor--a new mechanism for an old drug. - Karpe, F; Frayn, K (2004)
CONTEXT: Non-esterified fatty acids in plasma originate from adipose tissue. Delivery of fatty acids to the liver provides the substrate for VLDL triglycerides. Insulin-sensitive organs, overburdened by high concentrations of non-esterified fatty acids, may develop resistance to insulin action. In addition, insulin secretion from pancreatic beta-cells may be impaired by long-standing elevation of concentrations of non-esterified fatty acid in plasma. Normally, such concentrations fluctuate over the day depending on the transient suppression of lipolysis from adipose tissue by insulin released after meals. Diurnal concentrations of non-esterified fatty acid are often elevated in obesity, in particular in male-pattern upper-body fat accumulation. Nicotinic acid is the only drug that primarily lowers concentrations of non-esterified fatty acids and thereby lowers VLDL triglycerides. Nicotinic acid, or its analogues, seems to alleviate insulin resistance in the short-term whereas, paradoxically, the long-term effect is often the opposite. Suppression of lipolysis by nicotinic acid gives rise to a prominent rebound and the degree to which this occurs might explain this paradox. STARTING POINT: The exact cellular mechanism by which nicotinic acid exerts its antilipolytic effects has not been known until the recent discovery of a distinct G-protein coupled receptor. Nicotinic acid is a high affinity ligand, but the endogenous ligand is still unknown. Recently, Tina Rubic and colleagues (Biochem Pharmacol 2004; 67: 411-19) proposed a mechanism in which nicotinic acid stimulates cholesterol mobilisation from macrophages, thereby providing a potential link between regression of atherosclerosis and use of nicotinic acid. WHERE NEXT: Research on signalling through the nicotinic acid receptor might give rise to novel and more effective methods to interfere with fatty-acid metabolism, with insulin resistance, hyperlipidaemia, and atherosclerosis as target diseases.